Effect of Subcooling on Pool Boiling of Water from Sintered Copper Microporous Coating at Different Orientations - Seongchul Jun; Jinsub Kim; Seung M. You; Hwan Yeol Kim (Science and Technology of Nuclear Installations)
The subcooling effect on pool boiling heat transfer using a copper microporous coating was experimentally studied in water for subcoolings of 10 K, 20 K, and 30 K at atmospheric pressure and compared to that of a plain copper surface. A high-temperature thermally conductive microporous coating (HTCMC) was made by sintering copper powder with an average particle size of 67 μm onto a 1 cm × 1 cm plain copper surface with a coating thickness of ~300 μm. The HTCMC surface showed a two times higher critical heat flux (CHF), ~2,000 kW/m2, and up to seven times higher nucleate boiling heat transfer (NBHT) coefficient, ~350 kW/m2K, when compared with a plain copper surface at saturation. The results of the subcooling effect on pool boiling showed that the NBHT of both the HTCMC and the plain copper surface did not change much with subcooling. On the other hand, the CHF increased linearly with the degree of subcooling for both the HTCMC and the plain copper surface. The increase in the CHF was measured to be ~60 kW/m2 for every degree of subcooling for both the HTCMC and the plain surface, so that the difference of the CHF between the HTCMC and the plain copper surface was maintained at ~1,000 kW/m2 throughout the tested subcooling range. The CHFs for the HTCMC and the plain copper surface at 30 K subcooling were 3,820 kW/m2 and 2,820 kW/m2, respectively. The experimental results were compared with existing CHF correlations and appeared to match well with Zuber’s formula for the plain surface. The combined effect of subcooling and orientation of the HTCMC on pool boiling heat transfer was studied as well.